Climate-smart agriculture: A guide for farmers - Waswa, Boaz Shaban; Templer, Noel; Jalango, Dorcas; Nderi, Alex; Kinyua, Ivy Wambui (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This manual was developed as a training guide to empower and equip members of the farmers’ cooperative with the essential knowledge, skills, and best practices required to adopt and implement CSA technologies and Good Agricultural Practices (GAPs).